Platelet Rich Fibrin (PRF) in the Management of Osteonecrosis of the Jaw: A Narrative Review (Update Dental College Journal, 2025)
Introduction: Osteonecrosis of the jaw (ONJ) refers to a persistent condition of bone death within the maxillofacial region lasting in excess of eight weeks, frequently linked to therapeutic interventions involving radiation and antiresorptive or anti-angiogenic agents. Regulatory guidelines issued by the American Association of Oral and Maxillofacial Surgeons in 2014 omitted endorsement of standard treatment protocols, underscoring the need for comprehensive review and analysis of current research. This narrative synthesis aims to summarize and evaluate existing empirical evidence on the use of platelet-rich fibrin (PRF) in patients diagnosed with ONJ. Method: A search of English-language literature on PRF research on osteonecrosis of the jaw (ONJ) was conducted using the PubMed (Medline) database from 2014 to 2023. The search included randomized controlled trials, clinical trials, observational prospective studies, case reports, retrospective studies, cohort studies, and case series, with review articles excluded. The use of PRF for the management of ONJ was covered in twenty research articles. Follow-up periods ranged from one and half months to 79 months. Result: The findings from the selected papers indicate a female predominance. The lower jaw showed site prevalence in this review. In summary, the last ten years' worth of research indicates that PRF may be helpful in the treatment of ONJ, with improvement in wound healing, pain, and infection rates documented. None of the papers included any reports of complications associated with PRF treatment. Nevertheless, methodological errors like small sample sizes and a absence of randomized controlled studies now limit the data. Conclusion: To develop evidence-based clinical suggestions and ascertain the effectiveness of PRF in the management of ONJ, more study is required.Update Dent. Coll. j: 2025; 15(1): 46-51